Reprogramming the Mechanism of Action of Chlorambucil by Coupling to a G-Quadruplex Ligand - Di Antonio, Marco (American Chemical Society, 2014)
[Image: see text] The nitrogen mustard Chlorambucil (Chl) generates covalent adducts with double-helical DNA and inhibits cell proliferation. Among these adducts, interstrand cross-links (ICLs) are the most toxic, as they stall replication by generating DNA double strand breaks (DSBs). Conversely, intrastrand cross-links generated by Chl are efficiently repaired by a dedicated Nucleotide Excision Repair (NER) enzyme. We synthesized a novel cross-linking agent that combines Chl with the G-quadruplex (G4) ligand PDS (PDS-Chl). We demonstrated that PDS-Chl alkylates G4 structures at low μM concentrations, without reactivity toward double- or single-stranded DNA. Since intramolecular G4s arise from a single DNA strand, we reasoned that preferential alkylation of such structures might prevent the generation of ICLs, while favoring intrastrand cross-links. We observed that PDS-Chl selectively impairs growth in cells genetically deficient in NER, but did not show any sensitivity to the repair gene BRCA2, involved in double-stranded break repair. Our findings suggest that G4 targeting of this clinically important alkylating agent alters the overall mechanism of action. These insights may inspire new opportunities for intervention in diseases specifically characterized by genetic impairment of NER, such as skin and testicular cancers.